2006
DOI: 10.1007/s00167-006-0161-3
|View full text |Cite
|
Sign up to set email alerts
|

Sclerosing polidocanol injections in mid-portion Achilles tendinosis: remaining good clinical results and decreased tendon thickness at 2-year follow-up

Abstract: The short-term results after treatment with sclerosing polidocanol injections have been shown to be good in patients with chronic painful mid-portion Achilles tendinosis. This study aimed to evaluate the longer-term effects on tendon thickness, structure and vascularity, patient satisfaction with treatment, and pain during tendon loading activity. Ultrasonography (US) + colour Doppler (CD) was used for evaluation of the tendon, and the patients graded the amount of pain during tendon loading activity on a VAS.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
126
3
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(137 citation statements)
references
References 18 publications
5
126
3
3
Order By: Relevance
“…In the Swedish studies, the investigators were able to detect neovessels in 100 % of the symptomatic tendons [1,26,37,38]. This observation was not supported by other researchers, who reported a percentage varying from 47 to 88 % [13,41,42,54].…”
Section: Diagnosismentioning
confidence: 82%
“…In the Swedish studies, the investigators were able to detect neovessels in 100 % of the symptomatic tendons [1,26,37,38]. This observation was not supported by other researchers, who reported a percentage varying from 47 to 88 % [13,41,42,54].…”
Section: Diagnosismentioning
confidence: 82%
“…Polidocanol sclerotherapy has shown good short-and mid-term response in chronic Achilles tendonopathy. Pain reduction and improvement in ultrasound appearance at 2-year follow-up has been recorded, but there are no RTC studies [41].…”
Section: Tendonosismentioning
confidence: 99%
“…However, studies have demonstrated a positive therapeutic effect in treating Achilles tendinopathy through the use of Doppler ultrasound guided polidocanol injections [Ohberg, 2002], and this effect appears to persist at 2 year follow-up [Lind, 2006]. Ohberg et al reported that the pain reducing effect was in the order of 80% pain reduction in approximately 80% of patients when using between one and five guided polidocanol injection sessions.…”
Section: Polidocanol Sclerotherapy Injectionsmentioning
confidence: 99%
“…The therapeutic use of isolated growth factors for specific musculoskeletal injury is still in its infancy, and is currently prohibited for competitive athletes under the World Anti-Doping Authority (WADA) code January, 2011. The evidence for the use of autologous blood products, including platelet rich plasma, to treat Achilles tendinopathy or other tendinopathies is scant and most well conducted clinical trials do not show evidence of effect [de Vos, 2010 andPaoloni, 2010]. However many facets of the use of these injections have not been established, including; what is the optimal blood product injection type, what is the optimal volume of injection, what is the optimal timing of injection after injury, what is the optimal number and spacing of injections (single injection versus injection series, and what the optimal rehabilitation is after injection.…”
Section: Autologous Blood Product Injectionsmentioning
confidence: 99%